Growth and stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111) - Düll, Fabian; Meusel, Manuel; Späth, Florian; Schötz, Simon; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Bayer, Andreas; Papp, Christian (Physical Chemistry Chemical Physics, 2019)
The h-BN nanomesh on Rh(111) is used as eggbox-like template for the formation of arrays of Pt nanoclusters with a narrow size distribution. Nanoclusters with sizes from 1 up to 50 atoms are prepared simultaneously in a wedge-like structure by depositing a coverage gradient on the h-BN nanomesh, and thus can be investigated under identical conditions. We studied the preparation and properties of these Pt nanoclusters of different size in situ by high-resolution X-ray photoelectron spectroscopy and scanning tunneling microscopy. For a Pt coverage of 0.1 ML, all pores of the h-BN nanomesh are filled with nanoclusters with a remarkably uniform cluster size of ≈12 Pt atoms per pore, and high stability up to 400 K. Above 0.2 ML Pt, the clusters are less stable. The coverage dependent analysis shows that for Pt coverages below 0.1 ML, the number of nanoclusters is smaller - and the number of empty pores higher - than expected for a simple hit and stick mechanism. We assign this behavior to an initially higher mobility of the Pt atoms in a hot precursor state.
CRIS-Team Scopus Importer:2019-10-11